STRUCTURE COMMUNITY OF MANGROVE IN EAST MORO VILLAGE DISTRICT OF KARIMUN, RIAU ISLANDS - Kartina '; Sofyan H. Siregar; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research on structure community of mangrove in East Moro Village District of Karimun in Riau Islands has been done in June 2014. The purpose of study was to determine the species composition and dominant species in the mangrove ecosystem of East Moro Village. The method used in the research was survey method. The stations were determined by purposive sampling in three stations. The transects were set along the 50 meters from the sea to land perpendicular coastline. The number of plots was 27 for each plot with the size of 10 x 10 m2 for tree criteria, sub-plots of 5 x 5 m2 for sapling criteria, and 2 x 2 m2 for seedlings criteria. The results of this study founded 12 species of mangrove in East Moro Village District of Karimun Riau Islands. The vegetation was dominated by species of R.apiculata with critical values ranged 125.46 to 72.29 % . The conditions of mangrove vegetation in East Moro Village was still at good condition, with the average density ranged from 3066.67 to 2922.22 Ind /ha.Keywords: East Moro village, Structure Community, Mangrove